A bi-level model and hybrid heuristic algorithm for the optimal location of prefabricated building industrial park. (November 2022) - Huang, Ruopeng; Li, Kaijian; Liu, Guiwen; Shrestha, Asheem; Chang, Ruidong; Tang, Xiaoya
Abstract: Optimal location for prefabricated building industrial park (PBIP) can significantly reduce the logistic cost, delivery time and environmental pollution of prefabricated and modular construction. PBIP site selection problems can be more complex than other location selection problems when considering the goals of the PBIP at a manager level and a costumer level. There is little to no research that has examined the bi-level model for PBIP site selection. Thus, this paper addresses this issue by constructing a quantitative bi-level programming model which considers the economic, traffic, and environmental constrains. Subsequently, combining the genetic algorithm and Partan Frank–Wolfe​ algorithm, a hybrid heuristic algorithm is constructed to calculate the model. An empirical analysis is then carried out in the case of Chongqing, China. The results clearly demonstrate the applicability of the model. Furthermore, the paper discusses the trade-off between transport costs and environmental benefits, and the impact of transport radius on transport schemes. The proposed model contributes to solving location–allocation problems. It considers road congestion and traffic distribution by combining the location–allocation model with the user equilibrium model. The model can aid planners in making more robust decisions for setting up new PBIPs, thus contributing to the sustainable development of prefabricated and modular construction. Highlights: A bi-level model for the location of prefabricated building industrial park is proposed. Economic, traffic, and environmental constrains are incorporated into the model. A hybrid heuristic algorithm is proposed to calculate the model. Location–allocation and user equilibrium model are combined to plan logistic path. Trade-off between transport costs and environmental benefits are discussed.